2014
DOI: 10.1080/13691058.2014.955825
|View full text |Cite
|
Sign up to set email alerts
|

Being perceived as ‘a real woman’ or following one's own convictions: a qualitative study to understand individual, family, and community influences on the place of childbirth in Busia, Kenya

Abstract: Despite potentially playing a key role in improving maternal and child health, including the prevention of mother-to-child transmission (PMTCT) of HIV, health facility delivery rates remain low in Kenya. Understanding how place of childbirth is determined is therefore important when developing interventions to improve safe motherhood and childbirth outcomes. As part of a qualitative study, we conducted 25 in-depth interviews with mothers (13) and healthcare staff (12) and held 10 focus group discussions with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Women who used or intended to use maternity care services faced challenges such as inadequate facility opening hours [25, 157]; non-availability of services [111, 129, 158], poor (perceptions of) providers’ competence or clinical skills [64, 74, 76, 110, 111, 123, 151, 158–160] and knowledge [76, 158, 160–162]; inadequate staffing levels [48, 59, 67, 76, 82, 104, 106–108, 111, 153, 155, 157, 162165] as well as previous experiences of unskilled birthing care from maternity care providers [29]. Generally, women expect to receive care promptly on reaching a health facility; therefore, long waiting times present a significant challenge to accessing health facility-based services [22, 29, 31, 53, 82, 87, 97, 107, 115, 123, 154, 155].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women who used or intended to use maternity care services faced challenges such as inadequate facility opening hours [25, 157]; non-availability of services [111, 129, 158], poor (perceptions of) providers’ competence or clinical skills [64, 74, 76, 110, 111, 123, 151, 158–160] and knowledge [76, 158, 160–162]; inadequate staffing levels [48, 59, 67, 76, 82, 104, 106–108, 111, 153, 155, 157, 162165] as well as previous experiences of unskilled birthing care from maternity care providers [29]. Generally, women expect to receive care promptly on reaching a health facility; therefore, long waiting times present a significant challenge to accessing health facility-based services [22, 29, 31, 53, 82, 87, 97, 107, 115, 123, 154, 155].…”
Section: Resultsmentioning
confidence: 99%
“…Costs of services were a deterrent to obstetric care utilisation for some service users [30, 33, 43, 55, 56, 65, 72, 74, 76, 83, 91, 100, 112, 114, 118, 121, 129, 134, 153], as was informal payments for services [110, 155]. Service costs is a particularly significant barrier for poorer rural populations which tend to be socioeconomically disadvantaged across sub-Saharan Africa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An evidence synthesis of studies from 16 low-income and middle-income countries and China revealed that mistreatment during childbirth is a powerful deterrent to facility-based childbirth. 13 Additionally, studies from Afghanistan, 14 Bolivia, 15 Ghana, 16 Kenya, 17 18 Tanzania, 19 Malawi 20 and India 21 have clearly reported disrespectful care at birth as a key deterrent to facility-based childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, when women were included in decision, but were not the sole decision-makers about where to give birth, they were more likely to have a facility birth. Research has shown that although women want to choose their birthplace based on safety and other grounds [39], for many women the decision to give birth at a health facility is not their own but involves their family as well as the community [40]. The women sometimes find that their right to choose their birthplace is compromised because of cultural and traditional practices [41].…”
Section: Women's Autonomymentioning
confidence: 99%